MERTK as a novel therapeutic target in head and neck cancer - von Mässenhausen, Anne (Oncotarget, 2016)
Although head and neck cancer (HNSCC) is the sixth most common tumor entity worldwide therapy options remain limited leading to 5-year survival rates of only 50 %. MERTK is a promising therapeutic target in several tumor entities, however, its role in HNSCC has not been described yet. The aim of our study was to investigate the biological significance of MERTK and to evaluate its potential as a novel therapeutic target in this dismal tumor entity. In two large HNSCC cohorts (n=537 and n=520) we found that MERTK is overexpressed in one third of patients. In-vitro, MERTK overexpression led to increased proliferation, migration and invasion whereas MERTK inhibition with the small molecule inhibitor UNC1062 or MERTK knockdown reduced cell motility via the small GTPase RhoA. Taken together, we are the first to show that MERTK is frequently overexpressed in HNSCC and plays an important role in tumor cell motility. It might therefore be a potential target for selected patients suffering from this dismal tumor entity.